Non-overt DIC in Cryptogenic Liver Abscess-associated Sepsis in Children: a Case Report and Literature Review - Qiang FU, Ting WANG, Xia YAN (Zhongguo quanke yixue, 2022)
Liver abscess is rare in children, which is caused by biliary tract disease, pyoderma, appendicitis or trauma. There is little available relevant epidemiological data. In particular, cryptogenic liver abscess is difficult to diagnose at the early stage due to unknown etiology, and few clinical manifestations such as persistent fever without obvious abdominal discomfort. A delayed diagnosis may be associated with septic shock and DIC, leading to poor prognosis. We reported the diagnosis and treatment of a child with non-overt DIC in sepsis associated with cryptogenic liver abscess induced by infection with methicillin-resistant Staphylococcus aureus. The case report and literature review indicate that cryptogenic liver abscess is a rare cause of sepsis in children, which should be considered as a potential causative factor of sepsis besides hematogenous infection when the site of infection could not be determined regardless of whether abdominal pain is present or not.